First records of Sirococcus conigenus causing shoot blight on Pinus peuce in Bulgaria - Margarita Georgieva; Georgi Georgiev; Plamen Mirchev; Sevdalin Belilov (Historia naturalis bulgarica, 2023)
Macedonian pine (Pinus peuce) is a southern Balkan Peninsula endemic, growing in high mountains of Bulgaria, between 1400 and 2100 m a.s.l. Stands of P. peuce form the upper tree line forest areas. During a survey in 2020-2022 on Macedonian pine natural stands and plantations in Bulgaria, symptoms of shoot blight were observed in the Pirin Mts, the Rila Mts and Mt Vitosha. The fungal pathogen Sirococcus conigenus was identified as the causal agent of the disease that appeared for the first time on Pinus peuce in Bulgaria and Balkan Peninsula. Incidence of blighted shoots on individual trees varied, but was as high as 70-80% in the Rila Mts and Mt Vitosha.